Guiding Students' Scientific Practice: Distinct and Common Roles for Teachers and Scientists. (19th February 2014) - Peker, Deniz; Dolan, Erin L.
Many science education programs involve scientists in K-12 education to support students' engagement in scientific practices and learning science process skills and scientific epistemologies. Little research has studied the actions of scientists in classrooms or how scientists' actions may (or may not) supplement or complement the actions of teachers. In this descriptive study, we explore how teachers and scientists, working in pairs, guide high school students in the practice of scientific experimentation. In particular, we study the ways by which teachers and scientists act independently and in concert to guide students in designing and conducting biology experiments with unknown outcomes. We analyzed video recordings of classroom instruction in two different school settings, focusing on teachers' and scientists' acts as they are manifested through their language-in-use during face-to-face interactions with students. We argue that scientists and teachers act to support students in scientific experimentation in both distinct and common ways influenced by the particular teaching acts they perform and distinct authority roles they possess in the classroom (e.g., classroom authority vs. scientific authority).